Cryptography algorithm for wireless channel of CBTC system - WANG Chao1; LIU Li-li1; NIU Zhi-hua2; SHI Xiang-yong1; ZHANG Huan-guo3 (Tongxin xuebao)
As to the disadvantages of RC4 which was used for CBTC system,a new cryptography algorithm based on Montgomery-form ECC was brought forward.Compared with the traditional Montgomery elliptic curve,the improved algorithm would resume the value of y-coordinate with more security.In addition,compared with the traditional ECC,it has faster computing speed and can effectively resist the timing attack and energy attack.The new Montgomery-form ECC algorithm has accelerated current ECC encoding speed and would make great improvement to the implementation of ECC in CBTC and other wireless communication.